Microsociety and Human Capital as Foundations for Public Service Innovation in the Non-Western Public Administration Perspective - Ida Bagus Shantih Ananda Wiradarma (Public Policy and Management Inquiry, 2025)
The evolution of public administration paradigms reflects a transition from Old Public Administration (OPA), which emphasizes hierarchy, to New Public Management (NPM), which prioritizes efficiency, and subsequently to New Public Service (NPS), which promotes citizen participation. However, these paradigms are rooted in Western contexts, making them not entirely suitable for non-Western countries such as Indonesia. This article examines Non-Western Public Administration (NWPA) as a more contextual alternative by highlighting two fundamental pillars, namely microsociety and human capital. A qualitative method based on literature analysis is employed to explore how these concepts shape an innovative ecosystem in public service delivery. The findings indicate that microsociety serves as a community-based participation arena that provides cultural legitimacy, collective action, and locally driven innovation. Meanwhile, human capital plays a crucial role in improving the quality of public officials and citizens’ capacity to actively engage in governance processes. The integration of both aspects results in public services that are more inclusive, adaptive, and sustainable, while strengthening social legitimacy and collective welfare. This article concludes that NWPA is not merely a conceptual alternative to Western paradigms but a practical necessity for developing public governance in Indonesia that aligns with local wisdom, responds to socio-cultural diversity, and remains relevant to future challenges.